Hybrid genres = L'hybridité des genres - Garane, Jeanne, 1960- (French literature series ;, 2018)
"The essays collected in this volume explore the ways in which hybridity functions in a wide variety of visual, musical, and written texts from France, the Francophone world, and beyond. Hybridity is defined here as an unexpected interaction or combination between two or more forms--whether literary, filmic, ethnic, generic or gendered. The volume covers works ranging from the 16th to the 20th centuries, from Pierre de Ronsard to Woody Allen. The essays demonstrate that rather than being a uniquely postmodern or postcolonial phenomenon, hybridity may be integral to creativity itself, leading to the conclusion that hybrid forms tend to challenge authority by proposing alternatives to existing power structures or questioning conventional ways of thinking and viewing the world"--